2019
DOI: 10.1038/s41598-019-46221-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of small heat shock proteins in exosomes from patients with gynecologic cancers

Abstract: Small Heat shock proteins (sHsp) are a group of chaperone proteins. Under conditions of stress, the expression of sHsp is increased. Therefore, they are implicated in the pathogenesis of various autoimmune-mediated disorders and cancer. The purpose of this study was to analyze sHsp expression in exosomes from patients with gynecologic cancers and correlate these results with markers of cytotoxic immune response. The study group included patients with ovarian cancer, endometrial cancer, and patients with endome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 37 publications
(34 reference statements)
1
45
0
1
Order By: Relevance
“…Secondly, knowing that cancer progression can be further exasperated by other external stimuli (i.e., nicotine and alcohol) further reiterates the need for better diagnostic tools [35]. Cappello and colleagues organized an elegant review that detailed important data illustrating the utility of exosomes in clinical studies [39]; however, this review highlighted the limited in vitro and clinical data related to the utility of exosomes and gynecological cancers [40]. As a model system, here, we evaluated the affect of alcohol administration over time on the cervical cancer cell line, HeLa.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, knowing that cancer progression can be further exasperated by other external stimuli (i.e., nicotine and alcohol) further reiterates the need for better diagnostic tools [35]. Cappello and colleagues organized an elegant review that detailed important data illustrating the utility of exosomes in clinical studies [39]; however, this review highlighted the limited in vitro and clinical data related to the utility of exosomes and gynecological cancers [40]. As a model system, here, we evaluated the affect of alcohol administration over time on the cervical cancer cell line, HeLa.…”
Section: Introductionmentioning
confidence: 99%
“… [169] Gynecologic cancers Serum and serum-derived exosomes Significantly higher level of sHSPB5/CRYAB in endometrial cancer patients compared to endometriosis patients. No significant difference in HSPB5, HSPB6/HSP20, HSPB8/HSP22 expression was found in serum-derived exosomes [170] HSP40 SCLC Serum Significantly higher level of autoantibodies to HSP40 in serum was found in lung cancer patients than in healthy controls [171] Chaperonins Ovarian cancer Serum No significant difference in the level of antibodies to HSPD1/HSP60 was found between patients with ovarian cancer and healthy women. Significantly higher concentration of antibodies to HSPD1/HSP60 was found in early stages of cancer than in control groups [172] Colorectal cancer Serum Elevated level of sHSP60 in colorectal cancer patients compared to controls.…”
Section: Membrane-bound and Secreted Forms Of Hsps In Cancermentioning
confidence: 88%
“…Despite the current uncertainties, circulating EVs and their molecular cargo can be considered a promising source of biomarkers for the early detection, diagnosis, monitoring, and follow up of different types of cancer. Unfortunately, unlike other tumors for which there is considerable information, such as glioblastoma and prostate, lung, ovarian, and breast cancers [72][73][74][75][76][77][78], only two studies have been reported on exosomal molecular chaperones in TCs and their potential applications [21,27]. The levels of Hsp27, Hsp60, and Hsp90 were increased in the exosomes from the plasma of PTC patients compared with the same patients after thyroidectomy and patients with benign goiter [21].…”
Section: Exosomes and Tcmentioning
confidence: 99%